Pengaruh Pembelajaran Terintegrasi Islam Dan Sains Terhadap Hasil Belajar Siswa Kelas XI MIPA 4 - ize, ulfa; Imam Nawawi; Ira Nurmawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. The integration of knowledge from an Islamic perspective continues to be developed by Islamic education scholars. This idea emerged as a response to the dualism or separation between religious and secular sciences, which later gave rise to a segregated education system. In Indonesia, this dichotomy is clearly reflected in the diversity of educational institutions. The idea of unifying science and Islam has long been a topic of discussion. Although the term